2015
DOI: 10.1111/hex.12405
|View full text |Cite
|
Sign up to set email alerts
|

A concept mapping study evaluating the UK's first NHS generic fatigue clinic

Abstract: ImportanceFatigue is a significant and debilitating symptom affecting 25% of the population. It occurs in those with a range of chronic diseases, can be idiopathic and in 0.2–0.4% of the UK population occurs in combination with other symptoms that together constitute chronic fatigue syndrome (CFS). Until recently, NHS clinical services only focussed upon CFS and excluded the majority of fatigued patients who did not meet the CFS diagnostic criteria. The CRESTA Fatigue interdisciplinary clinic was established i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 28 publications
1
16
0
Order By: Relevance
“…The service was subsequently evaluated, to identify and prioritise service needs of its patients. This was carried out using a group concept mapping (GCM) approach and was found to successfully meet patients' expectations [7]. This initial study confirmed that people want their fatigue and their associated symptoms to be taken seriously by clinicians and ultimately, to be 'believed'.…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…The service was subsequently evaluated, to identify and prioritise service needs of its patients. This was carried out using a group concept mapping (GCM) approach and was found to successfully meet patients' expectations [7]. This initial study confirmed that people want their fatigue and their associated symptoms to be taken seriously by clinicians and ultimately, to be 'believed'.…”
Section: Introductionmentioning
confidence: 81%
“…To ensure we continue to meet the needs of clinic patients and in light of the recently implemented changes, we believed it was important to re-evaluate the service using the same factors identified by patients and referrers as part of the original study [7]. These factors, or ideas, were identified through a brainstorming exercise involving clinic patients and clinician referrers.…”
Section: Sift Deskmentioning
confidence: 99%
See 1 more Smart Citation
“…Balancing the insights from research and practice can maximise the likelihood of interventions being feasible and acceptable, and of treatment addressing important issues to patients while overcoming previously identified limitations [76]. …”
Section: Introductionmentioning
confidence: 99%
“…A study analysing this new service, described as the UK's first NHS generic fatigue clinic, found it successfully met the majority of important needs and was popular with both users and referrers. 1 Patients using the service were generally much older than those found in specialist CFS clinics and had a high burden of chronic disease, suggesting the demand for this type of clinic may well increase in future decades as population demographics change.…”
mentioning
confidence: 99%